Bone as a Preferential Site for Metastasis. (15th January 2019) - Sowder, Miranda E; Johnson, Rachelle W
ABSTRACT: Bone marrow provides a unique microenvironment favoring the colonization and outgrowth of metastatic tumor cells. Despite the high incidence of bone metastasis in breast and prostate cancer patients, many of the molecular mechanisms controlling metastatic progression remain unclear. Several gene signatures associated with bone metastasis have been reported, but no metastasis‐specific gene alterations have been identified. Therefore, there has been considerable interest in understanding how the bone microenvironment impacts the behavior of disseminated tumor cells (DTCs) prior to and following colonization of the bone. Substantial evidence indicates that disruption of normal bone homeostasis by tumor‐derived factors establishes a premetastatic niche within the bone that favors DTC colonization. Following dissemination, bone resident cells and the surrounding stroma provide critical signals that support tumor cell colonization, survival, and eventual outgrowth. Clinical data suggest that patients can harbor DTCs for years to decades prior to developing overt bone metastases, suggesting a period of tumor dormancy occurs in the bone marrow. Several dormancy‐promoting factors have been recently identified; however, critical questions surrounding the molecular triggers and timing of tumor cell emergence from dormancy remain. Here, we review how metastatic tumor cells co‐opt the bone marrow microenvironment for metastatic progression and discuss emerging insights into how to more effectively target DTCs and prevent metastasis. © 2018 The Authors. JBMR Plus published by Wiley Periodicals, Inc. on behalf of American Society for Bone and Mineral Research